PERAN SISTEM PERADILAN DALAM MENJAWAB PELUANG DAN TANTANGAN UNTUK MENANGANI ANAK YANG BERHADAPAN DENGAN HUKUM - Rahayuningsih, Uut; Maharani, Adinda; Zadi, M. Fadhal; Patmawati, Novi (Cahaya Ilmu Bangsa, 2025)
Abstract Children as the next generation of the nation require special protection in the justice system, especially when dealing with the law. Indonesia has adopted a humanist approach through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), replacing the previous retributive policy that risked causing stigmatization and psychosocial disorders. The SPPA Law prioritizes restorative justice and diversion mechanisms to resolve children's cases outside the formal justice process, with a focus on restoring social relations, rehabilitation and reintegration. This study uses normative legal methods to analyze the legal framework, principles of child protection, and the implementation of the SPPA Law in national and international contexts. The results of the study show that diversion and restorative justice have the potential to reduce the negative impacts of the conventional justice system, such as stigmatization and recidivism, while ensuring children's rights to optimal growth and development. However, the implementation of the SPPA Law faces complex challenges, including the uneven understanding of law enforcement officers, limited supporting infrastructure and the stigma of society that still prioritizes punishment over a rehabilitative approach. In addition, community participation and synergy between institutions in the diversion process are often less than optimal, opportunities for strengthening the system lie in adapting international practices such as the Family Group Conference from New Zealand, as well as increasing the capacity of human resources and rehabilitation facilities based on children's. Keywords: Justice System, Children, Opportunities and Challenges. Abstrak Anak sebagai generasi penerus bangsa memerlukan perlindungan khusus dalam sistem peradilan, terutama ketika berhadapan dengan hukum. Indonesia telah mengadopsi pendekatan humanis melalui Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak (UU SPPA), menggantikan kebijakan retributif sebelumnya yang beresiko menimbulkan stigmatisasi dan gangguan psikososial. UU SPPA mengedepankan keadilan restoratif dan mekanisme diversi untuk menyelesaikan perkara anak diluar proses peradilan formal, dengan fokus pada pemulihan hubungan sosial, rehabilitasi dan reintegrasi. Penelitian ini menggunakan metode hukum normatif untuk menganalisis kerangka hukum, prinsip perlindungan anak, serta implementasi UU SPPA da lam konteks nasional dan internasional. Hasil kajian menunjukkan bahwa diversi dan keadilan restoratif berpotensi mengurangi dampak negatif sistem peradilan konvensional, seperti stigmatisasi dan residivisme, sekaligus memastikan hak anak untuk tumbuh kembang optimal. Namun, implementasi UU SPPA menghadapi tantangan kompleks, termasuk pemahaman aparat penegak hukum yang belum merata, keterbatasan infrastruktur pendukung serta stigma masyarakat yang masih mengutamakan hukuman ketimbang pendekatan rehabilitatif. Selain itu, partisipasi masyarakat dan sinergi antar lembaga dalam proses diversi sering kali kurang optimal, peluang penguatan sistem terletak pada adaptasi praktik internasional seperti Family Group Conference dari selandia baru, serta peningkatan kapasitas sumber daya manusia dan fasilitas rehabilitasi berbasis kebutuhan anak. Kata kunci: Sistem Peradilan, Anak, Peluang dan Tantangan.